EFEK PENGGUNAAN KAPSUL MARINE OMEGA-3 TERHADAP KADAR TRIGLISERIDA PADA PASIEN HIPERLIPIDEMIA - Ana Khusnul Faizah; Lestiono Lestiono; Amitasari Damayanti (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2021)
Dyslipidemia is a lipid disorder characterized by the abnormal value in lipid in blood plasma. The objective of this study was to analyze the effect of short term marine omega-3 supplement capsules on triglyceride level in outpatients with dyslipidemia in Teaching Hospital Surabaya. This was a cohort prospective study. There were two groups, namely pre and post intervention group. The intervention group was given capsule of marine omega-3 for a month. The TG value was measured in pre and post using marine omega-3 capsule. We had 12 outpatients in every group. There were no significant difference in plasma TG level within control and intervention group (p>0.05).